Development of an scAAVIGF-I gene therapeutic vector for the enhancement of cartilage repair - Hemphill, Daniel, author; Goodrich, Laurie, advisor; McIlwraith, C. Wayne, advisor; Samulski, R. Jude, committee member; Slayden, Ric, committee member; James, Sue, committee member (Colorado State University. Libraries, 2014)
In this work, we hypothesize scAAVIGF-I can be efficiently engineered and used as a gene therapeutic vector to transduce cartilage and synovium and elicit biochemical changes consistent with cartilage repair mechanisms. Here we show joint tissues are permissive to serotype specific, efficient AAV transduction. This is in agreement with previous in vitro and in vivo studies demonstrating AAV as an efficient vector for gene therapy. Interestingly, we show a clinically relevant occurrence of pre-existing, serotype specific AAV neutralization. After creation of an optimized scAAVIGF-I vector, we show transduction of chondrocytes results in significantly increased IGF-I levels that translate to biochemical changes in glycosaminoglycan and proteoglycan content. NextGen RNA transcriptome sequencing and PCR analysis revealed significant differential regulation of genes in pathways including cartilage biology and cell death, but not significant in other pathways associated with IGF-I treatment such as Wnt and Akt regulation. The problem addressed by this research is ultimately answered in that scAAVIGF-I can both efficiently transduce joint tissue and increase IGF-I concentrations sufficiently to cause biochemical changes indicative of healthy cartilage, and the pathways associated with upregulation of IGF-I gene therapy are revealed.
Keywords: cartilage; AAV; gene therapy; IGF-I